Atomic geography : a personal history of the Hanford Nuclear Reservation - Adams, Melvin R., 1941- (Washington State University Press, 2016)
"Perhaps the first environmental engineer at Hanford, Melvin R. Adams spent 24 years on its 586 square miles of desert terrain. His thoughtful vignettes recall challenges and sites he worked on or found personally intriguing. Adams helped determine the initial scope of the soil and solid waste cleanup. The Environmental Restoration and Disposal Facility today covers 107 acres and has a capacity of 18 million tons. His group also designed and tested a marked, maintenance-free disposal barrier. It uses natural materials that will remain stable for thousands of years. They expanded a network of groundwater monitoring wells to define contaminated plumes, assess treatment effectiveness, and provide relevant data to hydrologists. They also developed a pilot scale pump and treatment plant for use on a four-square-mile carbon tetrachloride plume. Adams shares his perspective on leaking high-level waste storage tanks, dosimeters, and Hanford's obsession with safety."--Provided by publisher.